Frequency of Maxillofacial Injuries Among Athletes-Members of Various Sports Federations in Iranform 1998-2001 - H Mahmoud Hasehmi (Tehran University of Medical Sciences, 2003)
Nowadays, sport injuries constitute a major part of social accidents. The aim of the presentstudy, was to investigate the frequency of maxillofacial injuries among athletes-members of differentsports federations in Iran from 1998-2001. For this reason files which was related to sport injuries of men and women athletes-members of sports federations were studied in Medical Federation of the Islamic Republic of Iran Sports Organization. The information were received through 26 medical organizations,located in different states of the country. The results showed that maxillofacial injuries constitute the major part of the sports injuries. In male athletes, football was the most important cause for maxillofacial injuries. However, mountain climbing and skiing play the least role in this field. Among female athletes,karate was the cause of the highest rate of maxillofacial sport injuries. Diving, mountain climbing and skiing cause the least number of maxillofacial accidents. Nasal fracture was the most common sport injury among Iraninan male and female athletes.